Installation of the Character of Love for the Country Through the Study (Study of Indonesian Labor Children in Malaysia) - Yulianto, Moch. Iman; Majid, Ikhwanudin Abdul; Cahyono, Hadi; Sunarto, Sunarto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The character of loving the motherland is how to act, and think, which shows respect for one's country. The way to convey this individuality is through learning Indonesian and PPKN subjects. The researcher aims to describe how to instill the character of loving the motherland in studio students and the influence of conveying the nature of loving the motherland through this theme. This research was carried out with qualitative research, namely a qualitative approach. Data was collected using observation, interviews, and documentation. After data collection, the data is analyzed and checked against what is described in the theory. The research results obtained are as follows. How to instill the character of loving the motherland through Indonesian language subjects. Instilling the character of loving the motherland with Indonesian subjects and Civics leads to improving attitudes and behavior to preserve Indonesian culture, especially speaking the right language and adhering to discipline. This value is related to the sign of the character of love for the motherland in learning studio students. It can be summarized that the overall effect is to increase students' enthusiasm for learning about language and create a feeling of pride in culture and education in Indonesia.